How to bring urban and global climate studies together with urban planning and architecture?. (November 2020) - Fallmann, Joachim; Emeis, Stefan
Abstract: Climate friendly urban planning plays a key role in climate change mitigation and adaptation and allows for sustainable development of living conditions for future generations. It has been long understood that measures such as urban greening, planted facades and roofs or highly reflecting building materials are able to dampen excess heat and help reducing energetic costs. Transferring scientific and often theoretical knowledge into actual urban planning however necessarily involves an interdisciplinary dialogue. This paper intends to provide a review of existing literature from a meteorological perspective in order to answer the question how results from urban climate studies can be linked to architectural design of future urban areas. Results from state of the art research are evaluated and critically addressed, hence providing a catalogue for urban planners and stakeholders which should serve as basis for a re-evaluation of the term 'smart city'. Graphical abstract: Image 1 Highlights: Hands-on for climate resilient urban planning from a meteorological perspective. Urban sustainability needs interdisciplinary exchange between disciplines. Atmospheric and Climate research needs to involve energetic and technical aspects. Review about interrelations among urban issues and their presence in life cycle studies. Micro-meteorology governs climate sensitive architecture; impacts on mesoscale.